Global Mobile Satellite Communications Theory For Maritime, Land and Aeronautical Applications - Ilčev, Stojče Dimov; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book discusses current theory regarding global mobile satellite communications (GMSC) for maritime, land (road and rail), and aeronautical applications. It covers how these can enable connections between moving objects such as ships, road and rail vehicles and aircrafts on one hand, and on the other ground telecommunications subscribers through the medium of communications satellites, ground earth stations, Terrestrial Telecommunication Networks (TTN), Internet Service Providers (ISP) and other wireless and landline telecommunications providers. This new edition covers new developments and initiatives that have resulted in land and aeronautical applications and the introduction of new satellite constellations in non-geostationary orbits and projects of new hybrid satellite constellations. The book presents current GMSC trends, mobile system concepts and network architecture using a simple mode of style with understandable technical information, characteristics, graphics, illustrations and mathematics equations. The first edition of Global Mobile Satellite Communications (Springer, 2005) was split into two books for the second edition-one on applications and one on theory. This book presents global mobile satellite communications theory.
Introduction -- Space Segment -- Transmission Technique -- Satellite Communication Equipment -- Antenna Systems for Mobile Satellite Applications -- Propagation and Interference Consideration -- Ground Segment -- Conclusion.
Keywords: Telecommunication; Electronics; Transportation engineering; Traffic engineering; Computer networks .; Law of the sea; International law; Aeronautics -- Law and legislation; Communications Engineering, Networks; Electronics and Microelectronics, Instrumentation; Transportation Technology and Traffic Engineering; Computer Communication Networks; Law of the Sea, Air and Outer Space